Workers' participation in safety and health at work - Khairiah, Soehod (Faculty of Management and Human Resource Development, 2008)
This paper focuses on the importance of getting workers involved in safety and health issues at work. Since modernisation and industrialisation have led to human loss and tragedy all around the world due to industrial accidents, safety practitioners and observers have widely agreed that the traditional belief that employers are solely responsible for the workers’ safety at work should have a new paradigm. To create a safe working condition, workers should be allowed to participate actively in safety and health matters and cooperate with the employers. Since they are closer to their work, it is felt that the workers themselves are the most qualified to make decisions about safety and job improvements. Evidence showed that various benefits could be yielded if workers work together with employers including the reduction of death and injury rates at work. However, to make workers’ participation in this field effective, several criteria are crucial. They are the legal support, management support, trade union support, training and the positive quality of the workers involved.